The Development of PowerPoint-iSpring Learning Media on Molecular Shapes for Class X SMA - Trieana Avelia; Guspatni Guspatni (Entalpi Pendidikan Kimia, 2022)
The material of molecular shape or geometry is chemical material that has abstract properties, resulting in students having difficulty understanding the material. Therefore we need a learning media that is able to help students understand the material and able to display modeling in the form of animations, videos and pictures of molecular shapes clearly. PowerPoint-iSpring ia a learning media that is able to display animations, videos, texts, images and quizzes that can help students understand the concept of learning materials correctly. This research aims to develop a valid PowerPoint-iSpring learning media on the material of molecular shapes in class X SMA. This research uses the Plomp model which was carried out until the prototype III stage (expert review and one to one evaluation). The validation of this learning media was carried out by 5 validators, 3 chemistry lecturers at FMIPA UNP and 2 chemistry teachers. The assessment was carried out on the content, contructs and media of the developed PowerPoint-iSpring learning media. The result of conten validity is 0,87. Construct validity is divided into 2 components, linguistic and presentationd components with average values of 0,83 and 0,86. While the validity of the media on the components of the media efficiency, button function and physical quality are 0,93:0,95 and 0,8. So that the result of the validity of content, constructs and media can be categorized as valid.